2014
DOI: 10.1103/physrevb.90.024306
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Si impurities in Ni under stress: A first-principles study

Abstract: We perform a first-principles study of the effect of strain on the migration of Si atoms in Ni. For that purpose, migration barriers are computed using the nudged elastic band method and attempt frequencies are computed using the direct force method. Good agreement is found with tracer diffusion experiments. We used the elastic dipole model to calculate effects of strain on migration barriers by performing calculations on unstrained cells, therefore reducing significantly the computing time. We validate this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…Previously, atomic-scale migration properties of Si impurities in Ni were computed using DFT 28 . In this fcc alloy, non-negligible solute-vacancy interactions are found up to the third NN sites thus requiring the calculation of sixteen frequencies to describe diffusion.…”
Section: Diffusion Of Si Impurities In Ni Under Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, atomic-scale migration properties of Si impurities in Ni were computed using DFT 28 . In this fcc alloy, non-negligible solute-vacancy interactions are found up to the third NN sites thus requiring the calculation of sixteen frequencies to describe diffusion.…”
Section: Diffusion Of Si Impurities In Ni Under Strainmentioning
confidence: 99%
“…We compute the elasto-diffusion tensor using the SCMF method. In the Ni(Si) alloy, the cross terms of the elastic dipole-which quantifies the effect of ε 12 shear strain on diffusionare all an order of magnitude smaller than the diagonal terms 28 . It was assumed in Ref.…”
Section: Diffusion Of Si Impurities In Ni Under Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicon and nickel vacancies have interactions out to the third shell. Garnier et al 28 found an attractive ∆g 1 = −0.0996 eV (Z 1 = 12), a small ∆g 2 = 0.0120 eV (Z 2 = 6) and a repulsive ∆g 3 = 0.0452 eV (Z 3 = 24).…”
Section: Mesoscale Modelmentioning
confidence: 99%
“…Indeed, for the special case of Ni-Si alloy, Garnier et al 28 have showed an interesting result that the derivatives of migration barriers with respect to volumetric strain ∂E m /∂ v is a constant for all types of atomic jumps in the system. Since the migration barriers have good linear dependences on the volumetric strain v in a larger strain range than that for L AB 28,29 , we use the following expression instead of Eqn.…”
mentioning
confidence: 99%